Early and widespread emergence of regional warming is robust to observational and model uncertainty - Jonah Shaw; Nathan Lenssen (Environmental Research Letters, 2025)
The ability to distinguish observed climate change from naturally arising climate variability is one of the most fundamental findings in climate science. Climate change emergence is a key statistic used to quantify the impact of human activities on climate and inform climate change mitigation strategies. Previous studies determining when climate change has emerged, however, do not account for the combined uncertainty from historical observations and climate models. Here, we show that the emergence of regional warming is early, widespread, and robust to observational and model uncertainty. Warming has emerged over more than 90% of the global land surface as of 2020, and had emerged over more than 50% of the earth’s land surface by 2000. Emergence occurs despite observational and model uncertainty creating delays of more than 10 years over 75% of the land surface. These conclusions demonstrate that accounting for multiple sources of uncertainty is necessary for robust detection of climate change emergence.